Immediate Effects of Thoracic Expansion Exercises on Breath-Holding Capacity in Adolescents: A Quasi-Experimental Study - Anita, Astri; Th. Kum, Siti Rakhmatia Paramita; Panai, Dewi Nurindah (Jambura Medical and Health Science Journal, 2026)
Introduction: Breath-holding time (BHT) is a practical indicator of respiratory endurance and thoracic function. Thoracic expansion exercises (TEE) are widely implemented to enhance chest mobility and ventilatory performance, particularly among adolescents involved in physical training. This study evaluated the short-term effects of TEE on breath-holding time.Method: A quasi-experimental pre–post design was employed with 30 participants aged 14–19 years. The sample consisted of 18 males (60%) and 12 females (40%), with a mean age of 16 ± 0.95 years. BHT was assessed before and after the intervention using a standardized digital timer. Participants completed a structured TEE protocol involving repeated deep-inhalation cycles with controlled thoracic expansion. Statistical analysis was performed using a paired-samples t-test at a 95% confidence level.Results: Mean BHT increased from 39.77 seconds at baseline to 47.04 seconds post-intervention. The paired t-test indicated a significant improvement following TEE (t = –4.194, p 0.05), demonstrating that the exercise effectively enhanced respiratory endurance in the short term.Conclusion: TEE produces a significant immediate improvement in breath-holding capacity among adolescents. These findings support the integration of TEE into school-based or training programs aimed at optimizing respiratory function. Longitudinal studies are warranted to examine long-term effects. Keywords: Adolescent health, breathing exercises, physiotherapy, quasi‑experimental study, respiratory endurance